Hobbot or there and back again - Tolkien J. R. R. (London Harper Collins Puplishers UK, 1978)
The journey through Middle-earth begins here with J.R.R. Tolkien's classic prelude to his Lord of the Rings trilogy.(3z(BA glorious account of a magnificent adventure, filled with suspense and seasoned with a quiet humor that is irresistible... All those, young or old, who love a fine adventurous tale, beautifully told, will take The Hobbit to their hearts.(3y$1 (BThe New York Times Book Review"In a hole in the ground there lived a hobbit." So begins one of the most beloved and delightful tales in the English language$1 (BTolkien's prelude to The Lord of the Rings. Set in the imaginary world of Middle-earth, at once a classic myth and a modern fairy tale, The Hobbit is one of literature's most enduring and well-loved novels. Bilbo Baggins is a hobbit who enjoys a comfortable, unambitious life, rarely traveling any farther than his pantry or cellar. But his contentment is disturbed when the wizard Gandalf and a company of dwarves arrive on his doorstep one day to whisk him away on an adventure. They have launched a plot to raid the treasure hoard guarded by Smaug the Magnificent, a large and very dangerous dragon. Bilbo reluctantly joins their quest, unaware that on his journey to the Lonely Mountain he will encounter both a magic ring and a frightening creature known as Gollum.s
Keywords: ENGLISH LITERATURE